Industrial Disputes and Negotiation Skills in Local Government Administration in Nigeria - Yero, Aliyu; Musa, Ibrahim (Kashere Journal of Politics and International Relations, 2023)
This paper examines industrial disputes and negotiation skills in local government administration in Nigeria. In particular, the paper looks at the concept, nature and dimension of industrial disputes, causes of industrial dispute, and the impact of negotiation skills and dispute resolution in Nigerian local government system. Using historical approach, the paper looked at evolution of industrial dispute in Nigerian local government system with a view to understanding how the present can be appreciated and prepare for the future. The unitary theory of industrial dispute was used to understand the social reality of both employee and employer as it related to workplace ethics. The paper found that negotiation skills is not prominent within the local government system in Nigeria, that most of the negotiations within the local government system is carried out by outsiders indicating a draught of negotiation skills within the local government system. Furthermore, trade unions within the local government system do not have adequate training on how to handle industrial disputes and when the need arise; negotiation skills for speedy resolution of incompatible goals. The paper recommends that regular communication between managers of local government and employees is very important in preventing industrial dispute. Also, regular training will help enhance the skills of local government employees for better performance. Importantly, fair policies, having effective mechanisms for resolving disputes and collaborative dialogue between local governments based unions and management will help in promoting harmonious workplace culture.